Introduction to Food Process Engineering - Smith, P. G. (Food Science Text Series, 2011)
Introduction to Food Process Engineering treats the principles of processing in a scientifically rigorous yet concise manner, and can be used as a lead in to more specialized texts for higher study. It is equally relevant to those in the food industry who desire a greater understanding of the principles of the food processes with which they work. Written from a quantitative and mathematical perspective, this textbook is not simply a descriptive treatment of food processing. The aim is to give readers the confidence to use mathematical and quantitative analyses of food processes. To further this goal, each chapter includes a large number of worked examples and problems, with solutions provided in the back of the book. The mathematics necessary to read this book is limited to elementary differential and integral calculus and the simplest kind of differential equation. This second edition includes two additional chapters, Mass Transfer Operations and Minimal Processing Technology, as well as numerous new and revised figures.